An Evaluation of Maintanence Perfomance at Tanah Kusir Public Cemetery, South Jakarta - Prang, Christian Dave; Semarajaya, Cokorda Gede Alit; Krisnandika, Anak Agung Keswari (Jurnal Arsitektur Lansekap, 2024)
The Tanah Kusir Public Cemetery is the largest public cemetery in South Jakarta, it makes Tanah Kusir public cemetery can be used as one of the lungs of the city of Jakarta because the public cemetery itself is one of the green open spaces in urban areas, but in Tanah Kusir public cemetery still has areas that are not well maintained, this can be caused by an ineffective working capacity. Work capacity is a person's ability to complete his work in an area with a certain time and work capacity is one of the important elements of the maintenance system. This study was conducted to assess the effectiveness of the work capacity in Tanah Kusir public cemetery using a survey method. The data collected is primary and secondary data. Data collection techniques used are observation, interviews and literature study. Interviews were conducted with the public cemetery and observations of 10 workers in each field of work such as pruning, sweeping and watering. Based on the results of research conducted, it is known that the maintenance system used is a continuous maintenance system and in the implementation of maintenance such as pruning, sweeping and watering, the performance of workers still does not meet the ideal standard of work capacity. The recommendation given by the author is the need for additional workers and evaluation of skills, maximizing work schedules and more thorough supervision during work.